Investigation of Exponential Dichotomy of Itô Stochastic Systems by Using Quadratic Forms - Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For linear stochastic systems, we obtain sufficient conditions for mean-square exponential dichotomy in terms of Lyapunov functions that are quadratic forms.